2006
DOI: 10.1590/s0101-81752006000200033
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive cycle of Mellita quinquiesperforata (Leske) (Echinodermata, Echinoidea) in two contrasting beach environments

Abstract: The reproductive cycle of the irregular echinoid Mellita quinquiesperforata (Leske, 1778) was studied in populations from two sand beaches with different morphodynamic conditions in Parana coast, from February 1992 through July 1994. Gametogenesis was described by histological and gonad index methods and the differences between both populations were observed in the extension of nutrient storage and spawning period. Both populations exhibited a main reproductive period during spring/summer and a nutrient storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…Para as regiões sul e sudeste são conhecidos diversos trabalhos enfocando o grupo como um todo (Krau 1950, Brito 1971, Hadel et al1999, Netto et al 2005, Ventura et al 2006, 2007, bem como estudos mais concentrados em classes específicas (Tommasi 1970b, Manso 1988a, b, c, d, 1989, 1993, Manso & Absalão 1988, Borges et al 2002, Borges & Amaral 2006-Ophiuroidea, Tommasi 1965, 1969b, MacCord & Duarte 2002-Crinoidea, Tommasi 1969a, Tiago & Ditadi 2001, Mendes et al 2006-Holothuroidea, Tommasi 1966, Tavares & Borzone 2006-Echinoidea e Tommasi 1970a. O conhecimento sobre a fauna de equinodermos na Região Nordeste ainda é considerado escasso, principalmente nos estados do Piauí, Maranhão, Paraíba e Alagoas.…”
Section: Introductionunclassified
“…Para as regiões sul e sudeste são conhecidos diversos trabalhos enfocando o grupo como um todo (Krau 1950, Brito 1971, Hadel et al1999, Netto et al 2005, Ventura et al 2006, 2007, bem como estudos mais concentrados em classes específicas (Tommasi 1970b, Manso 1988a, b, c, d, 1989, 1993, Manso & Absalão 1988, Borges et al 2002, Borges & Amaral 2006-Ophiuroidea, Tommasi 1965, 1969b, MacCord & Duarte 2002-Crinoidea, Tommasi 1969a, Tiago & Ditadi 2001, Mendes et al 2006-Holothuroidea, Tommasi 1966, Tavares & Borzone 2006-Echinoidea e Tommasi 1970a. O conhecimento sobre a fauna de equinodermos na Região Nordeste ainda é considerado escasso, principalmente nos estados do Piauí, Maranhão, Paraíba e Alagoas.…”
Section: Introductionunclassified
“…The size of the sand dollars was another favorable factor for their use as an indicator of the hydrological dynamics of Praia de Santos. Figure 4 shows a predominance of adult animals, with higher chances of reproducing before being released to the supra coast and dying [29][30][31][32][33][34] found that water turbulence induces behavioral responses to the transition of Pacific sand dollar larvae (Dendraster excentricus) from the planktonic to the benthic phase. This same phenomenon may not occur with the larvae of Melitta quinquesperforata, seen by the absence of younger individuals (below 4cm) that possibly occupy places distant from the surf zone of Santos beach.…”
Section: Discussionmentioning
confidence: 99%
“…A gonadal tissue fragment (1 cm²) was removed through a small incision made under one of the interambulacral plates (1 cm²) for routine histotechnique procedures for hematoxylin and eosin (H&E). In the gametogenesis events description (Nunes & Jangoux, 2004;Tavares & Borzone, 2006, diagnoses were used for both regular echinoids: Lytechinus variegatus (Lamarck, 1816) (Toxopneustidae: Camarodonta) and irregular: Echinocardium cordatum (Pennant, 1777) (Loveniidae: Spatangoida) and Mellita quinquiesperforata (Leske, 1778) (Mellitidae: Clypeasteroida).…”
Section: Methodsmentioning
confidence: 99%